The Effect of Kahoot! On Junior Secondary School Students’ Vocabulary Mastery: An Experimental Study - Ratih, Ratih; Rohimajaya , Nur Azmi; Munawaroh, Tatu (Regalia Institute, 2023)
The aimed of this research to investigate the significant effect of Kahoot application towards students vocabulary mastery at the eighth grade of MTs Al-Mu’min Cikeusik, Pandeglang academic year 2023/2024. This research was quantitative approach with quasi-experimental design. The research paper used the quantitative approach and quasi-experimental design. This research was conducted from July-august, The technique in choosing the sample is cluster random sampling; and the researcher has chosen two classes are a control class and an experimental class This research consisted of two variables namely Kahoot application media as independent variable and students vocabulary mastery as dependent variable, using pre-test and post-test control group design. The population of this research was eighth grade of MTs Al-Mu’min Cikeusik consisted of 42 students divided into two class. the sample of this research were VIII A (22 students) as experimental class and VIII B (20 students) as control class. In the Collecting data technique, the researcher gives pre-test and post-test. The score pre-test of control group are 1,210, the score pre-test of experimental class are 1,475. Then, the score post-test of control group are 1,405, the score post-test of experimental group are 1,850. To collect the data, the researcher used SPSS version 29. to know whether was any significant effect students’ vocabulary mastery, between the students who are taught by using Kahoot application as media and who are not. Therefore, From the explanation above, it can be concluded that Kahoot application an effective media for English teaching-learning. The result of this research showed that the students who were taught by using Kahoot! game got better score than the students who were taught by using traditional method. The researcher has found the result of Significant two-tailed = 0.001 < α 0.05.